2014
DOI: 10.1007/s00296-014-3043-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric properties of WOMAC index in Greek knee osteoarthritis patients: comparisons with both self-reported and physical performance measures

Abstract: This observational study aimed to examine the clinimetric properties of the Greek for Greece translation of the Western Ontario and McMaster Osteoarthritis Index (WOMAC(®)). One hundred and twenty-three patients with knee osteoarthritis (mean age 69.5 years) participated in the study. An extensive reliability study was carried out to assess WOMAC's internal consistency and repeatability (8-day interval). In addition, we examined the construct (convergent, nomological and known-groups) and criterion-related (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…Our results demonstrated that WOMAC scores were positively correlated with evening VAS and activity VAS. Similar results have been found by Papathanasiou et al 51 . This is the first study for the determination of the association of synovial prostanoid levels with local fat thickness and clinical status in knee OA patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that WOMAC scores were positively correlated with evening VAS and activity VAS. Similar results have been found by Papathanasiou et al 51 . This is the first study for the determination of the association of synovial prostanoid levels with local fat thickness and clinical status in knee OA patients.…”
Section: Discussionsupporting
confidence: 92%
“…Correlations between the FJS-12 and the total and subscale scores of the other questionnaires were analyzed using Pearson's product-moment correlation coefficient. In all validity analyses, the coefficient values were characterized as follows: 0.00-0.19 = poor, if any; 0.20-0.39 = fair; 0.40-0.59 = moderate; 0.60-0.79 = good; and 0.80-1.00 = high/strong [15,16]. The ceiling and floor effects of a scale are described as the percentages of patients, showing the best or worst possible score on the scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The Greek versions of the PROs Lower Extremity Functional Scale (LEFS-Greek), 27–29 Western Ontario and McMaster Osteoarthritis Index (WOMAC-Gr), 30,31 and the PPMs Timed Up & Go (TUG) test 32,33 and 9-stairs-ascend/desscend (9S-A/D) test 34 were also used in the present study (see Supplemental Material, Appendix).…”
Section: Methodsmentioning
confidence: 99%